Microbial Desalination cells for Water Desalination and Power Generation - Nahla Jassim Faduos; Ali Jwaid (Wasit Journal of Engineering Sciences)
There are several ways to improve the desalination process, one of which is to use various configurations and modify the MDCs' traditional design. This strategy improves a number of variables, including the desalination efficiency, the rate of current production, the rate of removal of COD, and the rate of removal of total dissolved solids (TDS) The purpose of this study is to test the concept that desalination and energy production, two activities that work in tandem during wastewater MDC operation, can enhance system performance overall and increase the system's suitability for large-scale applications. use three chambered microbial desalination cells fed with synthetic wastewater and inoculated with activated sludge and anaerobic aged sludge.MDC was able to eliminate more than 90% of the NaCl in a salt solution with an initial salt concentration of 10000mg TDS/L over the course of the 4-month procedure while also producing bioelectricity. Additionally, the desalinated water met the drinking water requirement in terms of TDS concentration, with a TDS concentration of 7.50 g TDS L/1 d/1 (volume of the salt solution). An utmost power density of 314.8 mW/m3 was generated by the MDC. The predicted results demonstrated acceptable agreement with experimental results with determination coefficients R2>90%.